2009
DOI: 10.1682/jrrd.2008.04.0058
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Quantitative sensory testing (QST) has been used to assess neurological function in various chronic pain patient populations. In the present study, we investigated the ability of QST to reliably characterize somatosensory dysfunction in subjects with spinal cord injury (SCI) and neuropathic pain by measuring mechanical, vibration, and thermal detection and pain thresholds. Test-retest reliability was determined based on data collected from 10 subjects with SCI and neuropathic pain who underwent QST on two occa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(9 citation statements)
references
References 59 publications
(116 reference statements)
1
8
0
Order By: Relevance
“…This result is consistent with studies in healthy, non-disabled subjects and in other patient populations (31,46). A study by Felix and Widerström-Noga examined vibration thresholds across two test sessions in a sample of SCI patients with neuropathic pain and a sample of non-disabled control subjects, and the results showed that the ICCs were in the substantial range (0.86-0.90) (25). Two other studies have remarked on the stability of VPTs obtained in persons with SCI (24,47).…”
Section: Reliabilitysupporting
confidence: 88%
See 4 more Smart Citations
“…This result is consistent with studies in healthy, non-disabled subjects and in other patient populations (31,46). A study by Felix and Widerström-Noga examined vibration thresholds across two test sessions in a sample of SCI patients with neuropathic pain and a sample of non-disabled control subjects, and the results showed that the ICCs were in the substantial range (0.86-0.90) (25). Two other studies have remarked on the stability of VPTs obtained in persons with SCI (24,47).…”
Section: Reliabilitysupporting
confidence: 88%
“…Subjects were asked to indicate by clicking the mouse as soon as they felt the vibratory sensation. The next trial started again from the baseline value, with the average of three successive trials (separated by 10 s each) (25) taken as the vibration perception threshold (VPT) for each site. To include data for analyses at sites where no sensation was evoked during testing, we recorded the maximum amplitude of the vibratory stimulus (cutoff value) (VPT=130 µm) (25).…”
Section: Testsmentioning
confidence: 99%
See 3 more Smart Citations